2023
DOI: 10.3390/molecules28041642
|View full text |Cite
|
Sign up to set email alerts
|

Ugi Four-Component Reactions Using Alternative Reactants

Abstract: The Ugi four-component reaction (Ugi-4CR) undoubtedly is the most prominent multicomponent reaction (MCRs) that has sparked organic chemists’ interest in the field. It has been widely used in the synthesis of diverse heterocycle molecules such as potential drugs, natural product analogs, pseudo peptides, macrocycles, and functional materials. The Ugi-4CRs involve the use of an amine, an aldehyde or ketone, an isocyanide, and a carboxylic acid to produce an α-acetamido carboxamide derivative, which has signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 95 publications
0
6
0
2
Order By: Relevance
“…A standard Ugi four-component reaction (Ugi-4CR) of an aldehyde, amine, isocyanide, and a carboxylic acid produces highly diverse peptidic structures A with up to four points of substitution ( Scheme 1 ) [ 26 27 ]. By replacing the carboxylic acid with a nucleophilic azide reagent XN 3 (generally TMSN 3 ), the Ugi-azide four-component reaction (UA-4CR) of an aldehyde, amine, isocyanide, and azide gives 1,5-disubstituted 1 H -tetrazoles (1,5-DS-1 H -Ts) B .…”
Section: Introductionmentioning
confidence: 99%
“…A standard Ugi four-component reaction (Ugi-4CR) of an aldehyde, amine, isocyanide, and a carboxylic acid produces highly diverse peptidic structures A with up to four points of substitution ( Scheme 1 ) [ 26 27 ]. By replacing the carboxylic acid with a nucleophilic azide reagent XN 3 (generally TMSN 3 ), the Ugi-azide four-component reaction (UA-4CR) of an aldehyde, amine, isocyanide, and azide gives 1,5-disubstituted 1 H -tetrazoles (1,5-DS-1 H -Ts) B .…”
Section: Introductionmentioning
confidence: 99%
“…Different review articles relating to the synthesis of quinoxalines [10,25–36] . have appeared in the literature, but in these review articles the update information relating to the synthetic methods involving isocyanide based multicomponent reactions have not been addressed, although some representative methods have been included up to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Different review articles relating to the synthesis of quinoxalines. [10,[25][26][27][28][29][30][31][32][33][34][35][36] have appeared in the literature, but in these review articles the update information relating to the synthetic methods involving isocyanide based multicomponent reactions have not been addressed, although some representative methods have been included up to some extent. The present review article includes update information on the synthetic methods involving isocyanide based multicomponent reactions in the construction of structurally diverse heterocyclic scaffolds, quinoxalines and fused quinoxalines.…”
Section: Introductionmentioning
confidence: 99%
“…However, the utilization of carboxylic acids could also be considered as a limitation of the reactions due to a finite number of readily available variations. Besides carboxylic acids, very few alternative acids were described 6,7 El Kaim et al reported some notable examples by using Oarylative compounds as a replacement of carboxylic acids in both Passerini and Ugi reactions to access α-aryloxy-amides, 8 as well as O-and N-arylamides 9 (Figure 1c). Subsequently, the use of other starting materials instead of carboxylic acids has been reported (Figure 1A).…”
mentioning
confidence: 99%
“…However, the utilization of carboxylic acids could also be considered as a limitation of the reactions due to a finite number of readily available variations. Besides carboxylic acids, very few alternative acids were described , …”
mentioning
confidence: 99%